One hundred and twelve lines: about drawing and process (Revista de Ensino em Artes, Moda e Design, 2024)
This visual essay presents a sequence of images that make up the narrative of a video in which I set out to draw 56 lines with my right hand and 56 lines with my left hand on two pieces of paper, using black oil chalk. This work was part of a solo exhibition in 2021 called Drawing Exercises, in which I sought to present questions of process that reveal how the artist produces his work, as well as situating the work in a blur between process and final work, between drawing and writing. The essay aims to present, both in image and text, these questions about the final work and the process, and their intrinsic and almost tautological relationship, as the author Pamela Lee defines it in reference to drawing.
Keywords: drawing; contemporany drawing; artistic process